2019
DOI: 10.3389/fpsyg.2019.01356
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Climate(s), Organizational Identification, and Employees’ Behavior

Abstract: Ethical climate defines what is correct behavior and how ethical issues should be handled within organizations. For this reason, it plays a key role in organizational life. We relied on the social identity approach to compare the effects of two specific ethical climates – an ethical climate of self-interest vs. friendship – on employees’ reactions. In two scenario-based experiments ( N 1 = 152 and N 2 = 113), participants were asked to ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 56 publications
(82 reference statements)
3
59
0
1
Order By: Relevance
“…Employees' behavior, including OCB, was positively affected by the ethical climate through the social identity approach (Pagliaro et al, 2018). Ethical climates such as friendship utilizing the social identity approach projected better behaviors and attitudes of employees concerning many outcomes including turnover intention (Teresi et al, 2019). Studies also found that organizational justice theory impacts the effects on OCB through perceived restorativeness (Bellini et al, 2019).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Employees' behavior, including OCB, was positively affected by the ethical climate through the social identity approach (Pagliaro et al, 2018). Ethical climates such as friendship utilizing the social identity approach projected better behaviors and attitudes of employees concerning many outcomes including turnover intention (Teresi et al, 2019). Studies also found that organizational justice theory impacts the effects on OCB through perceived restorativeness (Bellini et al, 2019).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Work changes and leadership make no exception, becoming a dynamic and constantly evolving concept retaining primary importance from a strategic point of view (Teresi et al, 2019). Genuine leadership can no longer be limited to the mere proclamation of values to be followed, but it rather represents a shared function through which the leader can manage people and processes on a daily basis, through a distribution of power (Hall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy rights are basic human rights respected by empathic concerns. Given consumers' high identification with underdog brands, they may require the same moral standards and perspective-taking from these brands as they do for people (Waytz et al, 2010;Kwak et al, 2017;MacInnis and Folkes, 2017;Kouchaki et al, 2018;Lin and Huang, 2018;Teresi et al, 2019). On the other hand, consumers do not necessarily hold top-dog brands to such moral standards or expect them to make efforts to be perspective of others' autonomy rights.…”
Section: Introductionmentioning
confidence: 99%